Ruptur Kornea dan Prolaps Iris Oculi Sinistra et causa Trauma Tumpul : Sebuah Laporan Kasus - Gandaninata Yushan, Shina Megaputri; Sella, Martha; Juwita, Ratna (CV. Jasa Sukses Abadi, 2023)
Corneal rupture is an injury that affects the entire thickness of the corneal wall due to blunt trauma. A 32-year-old man came to the eye clinic at RSUD A Dadi Tjokrodipo with complaints of red left eye accompanied by sudden decreased vision since 3 weeks ago after being hit by a rock while working to cut grass with an electric lawn mower. The patient complained of red left eye, sudden blurry vision after an incident that persisted and did not increase, pain that spread to the back of the head, glare when exposed to light, and excessive tears. Ophthalmological status showed right eye vision 20/30, left eye vision 20/100. Palpation intraocular pressure in the left eye increased, while the right eye was normal. In the left eye there was a ciliary injection, the cornea was clear and appeared to be torn at 7 o'clock, the iris was prolapsed, the pupil looked oval drawn towards the lip of the wound, the lens was clear. The patient was diagnosed with corneal rupture and left iris prolapse. The operative treatment performed on this patient was corneal repair and repositioning of the left iris. The non-operative treatment used was gentamicin 0.3% eye drops 6x1 drops, 1% atropine sulfate eye drops 4x1 drops, mefenamic acid tablets 3x500 mg. Prognosis of this patient are quo ad vitam ad bonam, quo ad fuctionam dubia ad bonam, dan quo ad sanationam dubia ad bonam.